Transforming management education: blended learning, international collaboration, and pedagogical innovation—current trends and future directions - Bleicher, Juergen; Velinov, Emil; Adebola, Sunday (Frontiers in Education, 2025)
IntroductionBlended learning has emerged as a key strategy in management education, combining face-to-face teaching with digital tools to enhance flexibility, engagement, and skill development. When integrated with international cooperation projects, it enables pedagogical innovation and better prepares students for the complexities of global business environments.MethodsThis study employs quantitative analysis of course performance and engagement data to assess the impacts of blended learning combined with international collaboration. It draws on contemporary practices such as Collaborative Online International Learning (COIL), virtual exchange, and interdisciplinary teamwork to evaluate curriculum design, student outcomes, and institutional strategies.ResultsFindings demonstrate that blended learning facilitates the development of cross-cultural communication, ethical reasoning, and adaptive problem-solving skills. Technology-based experiential learning components like virtual internships, case simulations, and immersive platforms significantly enhance student engagement. However, challenges including digital inequities, resistance to pedagogical change, and the design complexity of effective blended environments persist.DiscussionAddressing these challenges requires targeted faculty training, robust infrastructure, and supportive policies. Future opportunities include leveraging artificial intelligence for personalized learning, gamification for increased engagement, and data analytics for real-time feedback. The study also highlights the critical role of academia–industry partnerships in creating impactful learning experiences. Ultimately, integrating blended learning with international collaboration advances management education toward more sustainable, inclusive, and practice-oriented models suited for a globally interconnected economy.